Amazing fish - Head, Honor (Pleasantville, NY : Gareth Stevens Pub., 2008)
Explores the life cycle of fish--such as tiny sea horses and giant hammerhead sharks--and discusses their behaviors and physical characteristics. Includes diagrams, fact boxes, and a glossary.
First published in Great Britain in 2007 by ticktock Media.
Includes index.
4.8
3-6
Keywords: Fishes -- Juvenile literature; Fishes -- Life cycles -- Juvenile literature; Fishes; Fishes -- Life cycles; Fishes; Fishes -- Life cycles